Peningkatan Kapasitas Produksi UMKM Pengolah Pentol Ayam melalui Diversifikasi Olahan Bakso Ikan Patin di Masa Pandemi Covid-19: Increased Production Capacity of Chicken Meatballs Processing SMEs through Diversification of Processed Catfish Meatballs during the Covid-19 Pandemic - Khotimah, Iin Khusnul; Fitrial, Yuspihana; Putri, Yasmin Finivera; Putri, Rizqina Ananda (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
Micro, Small, and Medium Enterprises (MSMEs) "Cici" savory chicken sticks are local food-based community businesses in Sekumpul Village, Martapura District, Banjar Regency, South Kalimantan. When facing the Covid-19 outbreak, their business has stopped operating for the last four months because the price of raw chicken is very high. Therefore, it is necessary to provide other technological innovations so that they can continue to develop these businesses. The potential of catfish as a raw material for chicken substitutes in this village is available because the price is lower and easy to obtain at the Martapura market. The purpose of this activity is to utilize catfish in meatball processing. The methods used are counseling, demonstration, participatory and mentoring. The results obtained from the implementation of service are partners can utilize catfish as an effort to use cheaper and easier raw materials in meatball processing, increase chicken meatballs production capacity through processing catfish meatballs, and processing catfish meatballs as a diversification solution for processed meatball products with fill healthy vegetables in the face of the Covid-19 pandemic.